Nanoscience in food and agriculture. 4 - Ranjan, Shivendu; Das Gupta, Nandita; Lichtfouse, Eric (Sustainable agriculture reviews, 2017)
This book presents comprehensive reviews on the principles, design and applications of nanomaterials in the food, water and pharmaceutical sectors. It is the fourth volume on Nanoscience in Food and Agriculture published in the series Sustainable Agriculture Reviews. It focuses on different aspects of the rapidly emerging area of nanotechnology. Nanomaterials are not new they have always occurred in nature, but what is new is the methods that allow the synthesis of unprecedented nanomaterials with tailored, finely tuned properties, which open the way for numerous applications in diverse fields. In particular, the high-surface-to-volume ratio of engineered nanomaterials makes them often more efficient than those found in nature. While nanomaterials are being commercialized in various sectors, they are only slowly being used in the food industry and their use is still a topic of debate. Research shows that nanomaterials improve bioavailability, shelf life and nutritional value by reducing nutrient loss and they are essential in active packaging, also known as intelligent or smart packaging, which helps extend shelf life, monitor freshness, display information on quality, and improve safety and convenience. Nevertheless, the potential toxicity of new nanomaterials should be studied before they are used in consumer products.